2021
DOI: 10.1016/j.breast.2021.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Survival patterns of invasive lobular and invasive ductal breast cancer in a large population-based cohort with two decades of follow up

Abstract: Survival patterns of invasive lobular and invasive ductal breast cancer in a large population-based cohort with two decades of follow up

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…[89][90][91][92] ILC appears to have a survival advantage compared to IBC-NST in the first 10-15 years after surgery; however, prognosis is worse for patients with ILC after this period. 90,92 In addition, patients with ILC are more likely to undergo mastectomy and have positive margins at surgical excision. 93 Large-scale studies have reported lower rates of pathological complete response to neoadjuvant therapy in ILC compared to IBC-NST, although this difference was no longer seen when cases were adjusted for tumour size, grade and ER/HER status in some series.…”
Section: Diagnosis Of Lobular Carcinoma and Clinical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[89][90][91][92] ILC appears to have a survival advantage compared to IBC-NST in the first 10-15 years after surgery; however, prognosis is worse for patients with ILC after this period. 90,92 In addition, patients with ILC are more likely to undergo mastectomy and have positive margins at surgical excision. 93 Large-scale studies have reported lower rates of pathological complete response to neoadjuvant therapy in ILC compared to IBC-NST, although this difference was no longer seen when cases were adjusted for tumour size, grade and ER/HER status in some series.…”
Section: Diagnosis Of Lobular Carcinoma and Clinical Implicationsmentioning
confidence: 99%
“…27,88 However, studies have shown that ILC has a different clinical presentation, prognosis and recurrence pattern with a predilection for bone and atypical sites for breast metastasis, such as the gastrointestinal tract, peritoneum and gynaecological tract. [89][90][91][92] ILC appears to have a survival advantage compared to IBC-NST in the first 10-15 years after surgery; however, prognosis is worse for patients with ILC after this period. 90,92 In addition, patients with ILC are more likely to undergo mastectomy and have positive margins at surgical excision.…”
Section: Diagnosis Of Lobular Carcinoma and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ER+ ILC and IDC tumors are treated clinically as a single disease (9), recent studies have established ER+ ILC as a distinct disease with unique sites of metastasis, frequent presentation of multifocal disease, delayed relapses, and decreased long-term survival compared to ER+ IDC tumors (10)(11)(12)(13)(14). Large-scale studies from The Cancer Genome Atlas (TCGA) and the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) have reported genomic and transcriptomic analyses on resected IDC and ILC tumors (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, ILC tumors have an indolent clinical course and grossly manifest as ill-defined masses or architectural distortion [ 5 ]. Additionally, ILC is generally more difficult to detect through standard imaging modalities such as mammography, Fluorodeoxyglucose-Positron Emission Tomography (FDG-PET), or ultrasounds compared to IDC [ [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%